The Critical Policy Geography of School Choice: Spatial Inequity and Segregation in Montréal - Yoon, Ee-Seul; Barrett DeWiele, Corinne (International Journal of Education Policy and Leadership)

(untitled) (Simon Fraser University, University of Delaware, Phi Delta Kappa International, 2025)
This study examines the impact of school choice policy on spatial inequity and the segregation of secondary schools in Montréal, Canada’s second-largest city. A critical policy geography perspective is applied to understand the significance of spatial locations of secondary schools and their programs of choice. This study utilizes Canadian census data, student enrolment data, and information about schools and school choice from government, district, and school websites. These various data sets are used primarily to generate layers on maps that facilitate critical geospatial analysis of school choice patterns. Our analysis illuminates the inequitable distribution of school choice programs in spatial terms. We also illustrate how spatial inequity reinforces segregation, as those with greater resources are more likely to enroll in schools in high-status neighbourhoods.